Influence of L-Tryptophan and L-Threonine in the Feed with Various Protein Levels on the Growth Performance and Morphology of the Ileum of Native Chickens Aged 1-8 Weeks - Charles Venirius Lisnahan; Oktovianus Rafael Nahak (Livestock and Animal Research, 2026)
Objective: The aim of this research was to find the influence of L-Threonine and L-Tryptophan in the feed, with various protein level, on the growth performance and ileum morphology of 1-8 weeks old native chicken.Methods: This research used 252 days old chick native chickens. This research also used 3x3 factorial design which was 3 level of threonine and tryptophan amino acid (0.15% L-tryptophan + 0.50% L-Threonine, 0.20% L-tryptophan + 0.75% L-Threonine and 0.25% L-tryptophan + 1.00% L-Threonine) and 3 levels of protein (15%, 17% and 19%). Each of the treatment combination was repeated 4 times. The collected data were analyzed using the Two-way ANOVA technique by the means of SPSS program (version 25). The average of significant difference in the treatment was used in the Duncan test at probability level of P<0.05.Results: The results of this research showed that interactions between amino acid and crude protein were not significant for all variables observed. The level of amino acid significantly affected the body weight gain, feed intake, feed conversion, carcass percentage, and villi height of native chicken ileum (P<0.05). So did the increment of protein level; it significantly affected the growth performance, villi height, and crypt depth of ileum (P<0.05).Conclusion: It was concluded that the higher the amino acid (threonine and tryptophan) and the crude protein level in the feed, the higher the growth and ileum profile of native chickens (1-8 week old).